Association Study between Cervical Lesions and Single or Multiple Vaccine-Target and Non-Vaccine Target Human Papillomavirus (HPV) Types in Women from Northeastern Brazil. - Bárbara Simas Chagas; Manola Comar; Manola Comar; Ana Pavla Almeida Diniz Gurgel; Sérgio Paiva; Silva Seraceni; Antonio Carlos de Freitas; Sergio Crovella (PLoS ONE, 2015)
We performed an association between high-grade squamous intraepithelial lesions (HSIL), low-grade squamous intraepithelial lesions (LSIL) and single or multiple vaccine-target as well as non-vaccine target Human papillomavirus (HPV) types. Using bead-based HPV genotyping, 594 gynecological samples were genotyped. An association between squamous intraepithelial lesion (SIL) and presence of HPV16, 18, 31, 58 and 56 types were calculated. The risk was estimated by using odds ratio (OR) and 95% of confidence intervals (CI). A total of 370 (62.3%) women were HPV positive. Among these, 157 (42.7%) presented a single HPV infection, and 212 (57.3%) were infected by more than one HPV type. HPV31 was the most prevalent genotype, regardless single and multiple HPV infections. Single infection with HPV31 was associated with LSIL (OR=2.32; 95%CI: 1.01 to 5.32; p=0.04); HPV31 was also associated with LSIL (OR=3.28; 95%CI: 1.74 to 6.19; p= 0.0002) and HSIL (OR=3.82; 95%CI: 2.10 to 6.97; p<0.001) in multiple HPV infections. Risk to harbor cervical lesions was observed in multiple HPV infections with regard to the HPV56 (OR=5.39; 95%CI: 2.44 to 11.90; p<0.001for LSIL; OR=5.37; 95%CI: 2.71 to 10.69; p<0.001) and HPV58 (OR=3.29; 95%CI: 1.34 to 8.09; p=0.0091 for LSIL; OR=3.55; 95%CI: 1.56 to 8.11; p=0.0026) genotypes. In addition, women coinfected with HPV16/31/56 types had 6 and 5-fold increased risk of HSIL (OR=6.46; 95%CI: 1.89 to 22.09; p=0.002) and LSIL (OR=5.22; 95%CI: 1.10 to 24.70; p=0.03), respectively. Multiple HPV infections without HPV16/18 has 2-fold increased risk of HSIL (OR=2.57; 95%CI: 1.41 to 4.70; p=0.002) and LSIL OR=2.03; 95%CI: 1.08 to 3.79; p=0.02). The results of this study suggest that single and multiple vaccine target as well as non-vaccine target HPV types are associated with LSIL and HSIL. These finding should be taken into consideration in the design of HPV vaccination strategies.